Inflammation-inducing Factors of Mycoplasma pneumoniae - Shimizu, Takashi (Frontiers in Microbiology, 2016)
Mycoplasma pneumoniae, which causes mycoplasmal pneumonia in human, mainly causes pneumonia in children, although it occasionally causes disease in infants and geriatrics. Some pathogenic factors produced by M. pneumoniae, such as hydrogen peroxide and Community-Acquired Respiratory Distress Syndrome (CARDS) toxin have been well studied. However, these factors alone cannot explain this predilection. The low incidence rate of mycoplasmal pneumonia in infants and geriatrics implies that the strong inflammatory responses induced by M. pneumoniae coordinate with the pathogenic factors to induce pneumonia. However, M. pneumoniae lacks a cell wall and does not possess an inflammation-inducing endotoxin, such as lipopolysaccharide (LPS). In M. pneumoniae, lipoproteins were identified as an inflammation-inducing factor. Lipoproteins induce inflammatory responses through Toll-like receptors (TLR) 2. Because Mycoplasma species lack a cell wall and lipoproteins anchored in the membrane are exposed, lipoproteins and TLR2 have been thought to be important for the pathogenesis of M. pneumoniae. However, recent reports suggest that M. pneumoniae also induces inflammatory responses also in a TLR2-independent manner. TLR4 and autophagy are involved in this TLR2-independent inflammation. In addition, the CARDS toxin or M. pneumoniae cytadherence induces inflammatory responses through an intracellular receptor protein complex called the inflammasome. In this review, the inflammation-inducing factors of M. pneumoniae are summarized.